HUBUNGAN KARAKTERISTIK PETANI DENGAN PERSEPSI PETANI TERHADAP SISTEM RESI GUDANG KOMODITAS PADI (ORYZA SATIVA) - Kurnia Bayu Pratama; Suminah Suminah; Supanggyo Supanggyo (Universitas Sebelas Maret, 2016)
Warehouse receipt system has a very useful role for the life of farmers, particularly in assisting farmers in marketing their results, provision of warehousing facilities and credit. This research was conducted in Sub District Jaten by using descriptive analytical method. The research location was determined purposively in Sub District Jaten, because the warehouse and management of warehouse receipt system in Sub District Jaten. Respondents as much as 60 respondents using teknik proportional random sampling. While the analytical methods used to analyze using Spearman Rank Correlation Test Keofisien (rs). Results of Spearman Rank analysis and test of significance at 95% confidence level is obtained the result that the relationship between the characteristics of farmers with farmer perceptions is that there is no significant, relationship between the area of land tenure to farmers with perceptions there is a significant, correlation between perceptions and of formal education with farmer perceptions there was a significant, relationship between non-formal education, experience, social environment, economic environment, and information with farmers' perception of warehouse receipt system in commodities of rice in Sub District Jaten Regency Karanganyar there is a significant.